Role and Impact of Energy in the Business Cycle - HUYNH, Bao Tan (Institutional Knowledge at Singapore Management University, 2015)
Given the fundamental role of energy in the economy, the macroeconomic literature contains a large body of work on the impact of oil/energy on the business cycle, with much of the attention focusing on energy supply shocks, mostly modeled as exogenous oil/energy price increases. And yet, the oil price hikes pre-2008 suggest that other shocks to the energy market may be the source of such instance of price disturbances, so that their effects on the economy are no longer predicted by exogenous energy supply shocks. In such scenario, it is no longer valid to treat energy price disturbances as exogenous shocks to an economic model that seeks to study the impact of energy on the business cycle.